A Study on Influencing Factors and Challenges of Ethics in Business in Indian Context - Jyoti Mishra (Management Journal for Advanced Research, 2023)
In order to survive and grow in the market, moral values are one thing which must be taken into consideration along with the vision set up by Organization. From a business point of view each and every organization tries to achieve the main goal, which obviously is to ‘maximize the profit’. But while doing so these organizations should also consider their moral, ethical and social obligations. Business ethics refers to the principles, values, and moral standards that guide the behavior and conduct of individuals and organizations within the business environment. As economies evolve and global markets expand, the role of ethical behavior in business becomes increasingly important. Ethics support indirectly to the growth of the Organizations. In this era of sustainability, ethics is the power in the hands of organizations to achieve sustainable practices. This research paper aims to explore the various influencing factors and challenges that impact ethical practices within the world of business. The study examines various internal and external elements affecting ethical decision-making processes among businesses, analyzes the implications of these factors on corporate behavior, and suggests potential strategies to promote ethical practices. It is an exploratory & descriptive study completed massively with the help of Secondary data. The paper encompasses the world of Ethics in Business & describes the associated factors & challenges. The Author has suggested a recommendary model stating the essence of ethics in business and the approaches required to achieve the same. The Author has considered industries at large and the same may be the limitations of the study as the inferences are indicative in nature rather exhaustive. Ethics have a strong role to play in the world of Business, this attempts to generate insights in this respect.